DAYAH CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN DAYAH TAHFIZUL QUR'AN ZURRIYATUL QUR'ANI AL-MA'ARIF LHOKSEUMAWE - muhadaruddin muhadaruddin; AlMuhajir AlMuhajir; M. Nazar (Journal of English Education and Social Science, 2023)
This study aims to explain the planning, implementation and supervision of the Dayah Tahfizul Qur'an Curriculum Zurriyatul Qur'ani Al-Ma'arif Lhokseumawe. This research is a field study (field research) with a qualitative approach using descriptive methods. this research uses the main data sources, namely dayah leaders, dayah managers, school principals at Dayah Tahfizul Qur'an Zurriatul Qur'ani Al-Ma'arif Lhokseumawe make a systematic, factual and actual description of the facts, nature and relationships between existing phenomena. Data collection techniques by means of in-depth interviews and text analysis. The research results obtained 1) The planning of the dayah curriculum in improving the quality of education in the Dayah Tahfizul Qur'an Zurriyatul Qur'ani Al-Ma'arif Lhokseumawe has been going well as stated in the division of tasks in the Dayah Tahfizul Qur'an Zurriyatul Qur'ani Al-Ma 'arif Lhokseumawe, so that the quality of dayah education continues to increase as expected, 2) The implementation of the dayah curriculum in improving the quality of education at Dayah Tahfizul Qur'an Zurriyatul Qur'ani Al-Ma'arif Lhokseumawe goes well, the implementation uses two curriculum and integrating it, namely the curriculum of the Ministry of Religion of the Republic of Indonesia with the Salafi Dayah Curriculum, and its implementation has been carried out in accordance with the management function, namely with the process of planning, organizing, implementing and supervising and evaluating by the leadership of the Dayah Tahfizul Qur'an Zurriyatul Qur'ani Al-Ma'arif Lhokseumawe, and 3) Oversight of the dayah curriculum management in improving the quality of education at Dayah Tahfizul Qur'an Zurriyatul Qur'ani Al-Ma'arif Lhokseumawe, there is internal supervision from the founders and leaders of the foundation in planning and implementing the curriculum which has also been going well, and external supervision from related agencies and the community has also been going well.